Snack bar Jawawut, Pisang Kepok, Ikan Belanak (Japisbell): Cemilan Sehat untuk Penderita Diabetes MelitusSnack bar Jawawut, Pisang Kepok, Ikan Belanak (Japisbell): Cemilan Sehat untuk Penderita Diabetes Melitus: Japisbell Snack bar (Millet, Kepok Banana, Mullet Fish): a Healthy Snack for Diabetes Mellitus Sufferers - Ginta Siahaan; Abdul Hairuddin Angkat; Emi Inayah; Lydia Fanny; Khanaya Annisa Hardianti (Universitas Airlangga, 2025)
Background: Diabetes mellitus (DM) is a metabolic disease that requires dietary adjustments, including snacking. Local foods such as millet seeds, kepok banana, and mullet fish have the potential to become snack alternatives in the form of Japisbell snack bars. Objectives: Analyzing organoleptic tests and chemical quality tests on Japisbell snack bars as an alternative snack for diabetes mellitus sufferers. Methods: The experimental research used a Completely Randomized Design (CRD) with 4 treatment formulations and 2 replications. Organoleptic tests were conducted by 60 semi-trained panelists using a hedonic scale. Color testing was also conducted using the CIE Lab system. Chemical quality analysis included GI, fiber, total antioxidants, flavonoids, and zinc. Data processing was analyzed using Kruskal-Wallis and Mann-Whitney. Results: Acceptability based on organoleptic test was found that treatment D, with a composition of 30 gs of millet, 70 g of kepok banana, and 20 g of mullet fish, was categorized as very preferred. Color testing reinforced with the CIE Lab system showed the position of L* 37.8; a* 4.4; b* 12.2, which describes a dark brown color. The selected treatment was examined, then found GI 58.03, fiber 6.67%, flavonoids 9.50 mg/100 g, zinc 4.0 mg/100 g, and total antioxidants 38.89 ppm. Conclusions: Acceptability of Japisbell snack bar formulation D with a composition of 30 g of millet, 70 g of kepok banana and 20 g of mullet with the characteristics of dark brown color, crunchy texture, savory taste and cake aroma with a relatively low GI content, high fiber and flavonoids and zinc, as well as a very strong total antioxidant content so that it has the potential as a snack for people with diabetes mellitus.